TEOREMA TITIK TETAP FUNGSI NONEKSPANSIF (FIXED POINT THEOREMS FOR NONEXPANSIVE MAPPINGS) - , APREYENI MARLINA FITRIYANI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In this final project, we discuss about fixed point theorems for nonexpansive mappings in complete metric spaces. First, we discuss about fixed point theorems for contraction mappings in complete metric spaces. Furthermore, we discuss about the sufficient conditions to ensure the existence of fixed points of contraction mappings in sub metric spaces of a complete metric space using homotopy for two contraction mappings. Especially, we discuss about the sufficient conditions to ensure the existence of fixed points of nonexpansive mappings in Hilbert spaces. In the last section, we discuss about the sufficient conditions to ensure the existence of fixed points of nonexpansive mappings in Banach spaces with uniformly convex structure.